Resort Hotel and Floating Cottage in Bogor Regency with a Biophilic Architecture Approach - Rahmawati, Adeli; Putra, RM Bambang Setyohadi Kuswarna; Diharto; Setyowati, Wiwit (Universitas Negeri Semarang, 2024)
Resort Hotel and Floating Cottage, is one of the tourist attractions that many people visit for vacation. The planning of the Resort Hotel and Floating Cottage utilizes the natural beauty in the form of lake and mountain views located in Cigombong District, Bogor Regency and the location is a Kawasan Ekonomi Khusus (KEK) so that the Public-Private-Community Partnership, operational model is applied, namely a partnership between the government, entrepreneurs, and the community. Tourism in Indonesia has an important role in driving national economic growth and improving people's welfare. The natural beauty spread across Indonesia has the potential for tourism development, especially for Resort Hotels and Floating Cottages. In its realization, there are facilities related to local culture so that the community can contribute. This Resort Hotel and Floating Cottage planning is classified as a 3-star Health Resort & Spa type with more complete facilities. In addition, because the planning of this Resort building utilizes the beauty of nature, the Biophilic Architecture approach was chosen which basically has the principle of building a good relationship between humans, nature, and buildings.